Chemistry of tourmalines in some pegmatites of São Jose da Safira area, Minas Gerais, Brazil - Bilal,E.; Cesar-Mendes,J.; Correia-Neves,J.M.; Nasraoui,M.; Kazuo-Fuzikawa (Journal of the Czech Geological Society, 1998)
The tourmaline group minerals (schorl to elbaite) typically occur in the Li-bearing pegmatites from the São Jose da Safira region (the Oriental Pegmatitic Province (OPP) in Minas Gerais State, Brazil). The Fe/Mn ratios of the tourmalines are compared to those measured in columbite-tantalite and garnet and decrease northward continuously from the beryl-bearing pegmatites to the spodumene-bearing ones. The Fe/Mn ratio has been used as a qualitative index of fractionation which seems to reflect the regional zoning of the pegmatites around a hidden granite body. The Fe/Mn ratio values correlate negatively with the Na and Li contents. The REE, Nb, Co and Zn contents are controlled by the mineral assemblages.
Keywords: tourmaline; behierite; columbite-tantalite; Brazil; Minas Gerais; Li-bearing pegmatite; fractionation